2D QSAR, PHARMACOPHORE AND DOCKING STUDIES OF MYCOBACTERIUM TUBERCULOSIS ENOYL ACYL CARRIER PROTEIN REDUCTASE INHIBITORS - Haripriya Munipalli (Journal of Global Pharma Technology, 2010)
InhA, the enoyl acyl carrier protein reductase is one of the key enzymes involved in the type II fatty acid biosynthesis pathway of M. tuberculosis. Discovery Studio 2.5 was used to carry out the current work. Different training sets and test sets were taken for QSAR and pharmacophore studies from a total of 116 molecules. In the present work, classical 2D QSAR (r2 = 0.913, Adj. r2 = 0.95 and cross-validated r2 = 0.90) models were developed for a series of 95 enoyl acyl carrier protein reductase inhibitors. This model was applied to successfully estimate activities of 14 test set molecules. Hiphop showed best fit with five features namely one hydrogen bond donor, three hydrophobic and one hydrophobic aromatic. The best hypothesis of hypogen run with 28 molecules consisting of four features namely two hydrophobic aromatic, one hydrophobic aliphatic and one hydrophobic, has a correlation coefficient of 0.914, a root mean square deviation of 1.166 and a cost difference of 80.23, suggesting that a highly predictive pharmacophore model was successfully obtained. The application of the model showed success in predicting the activities of few molecules in 54 known Mt EACP reductase inhibitors in our test set with a correlation coefficient of 0.847(r). The CDOCKER energies of two highly active inhibitors were -27.723 and -18.668, that of one moderately active inhibitor was -27.191 and of two low active inhibitors were and -2.581, -3.807. From 2D-QSAR, pharmacophore and docking studies the results have shown that Triclosan derivatives were proved to be highly potent inhibitors against Mycobacterium tuberculosis enoyl acyl carrier protein reductase.Keywords: Common feature pharmacophore; 3D-QSAR pharmacophore generation; Hip-hop; Hypogen; CDOCKER; Mycobacterium tuberculosis enoyl acyl carrier protein reductase (Mt EACPR); and 2D-QSAR.